A modified formula using energy system contributions to calculate pure maximal rate of lactate accumulation during a maximal sprint cycling test - Yang, W. H.; Park, S. Y.; Kim, T.; Jeon, H. J.; Heine, O.; Gehlert, S. (Frontiers in Physiology, 2023)
Purpose: This study aimed at comparing previous calculating formulas of maximal lactate accumulation rate (vLa.max) and a modified formula of pure vLa.max (PvLa.max) during a 15-s all-out sprint cycling test (ASCT) to analyze their relationships.